Nocturnal low irradiance pulses improve fruit yield and lycopene concentration in tomato - Gergoff Grozeff, Gustavo Esteban (2016)
Light is one of the most important factors modulating processes and sequences in plants life, like fruit ripening and the concentrations of water and lipid soluble antioxidants. The aim of this work was to evaluate the most effective frequency of low irradiance light pulses (LP) during the night and to analyze its effect on plant and fruit growth, as well as on modifications of concentrations of soluble sugar, amino acids, antioxidants and organic acids. LP of 15 min each were applied over the plants in a temperature controlled greenhouse after fruit set till they turned to mature red, with a frequency of 2 and 4 h. LP induced no changes in the typical maturation indexes such as soluble solid, total acidity, pH or firmness; meanwhile there was an 18% increase in fruit yield when plants were exposed to 15 min LP every 2 h during the night. Furthermore, by analyzing the tomato cluster receiving this LP treatment separately, the biomass of the fruit was found to have increased by 28% compared with the same cluster in control plants. In coincidence with this, fruit treated with a frequency of 2 and 4 h LP showed an increase in lycopene concentration, concomitantly with a rise in the proportion of red mature fruit harvested from the whole plant. On the other hand, there was a drop in the concentration of soluble sugars and free amino acids, possibly conducing to a decrease in water soluble antioxidants (ascorbic acid and glutathione) and citric and malic acids concentration. Overall, these results showed that nocturnal LP treatments improved fruit yield in tomato plants with higher amounts of lycopene, which indicate earlier fruit ripening.